2015
DOI: 10.1002/ajmg.a.36982
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive hypertrophic cardiomyopathy in an infant with Noonan syndrome with multiple lentigines: Palliative treatment with a rapamycin analog

Abstract: Noonan syndrome with multiple lentigines (NSML) frequently manifests with hypertrophic cardiomyopathy (HCM). Recently, it was demonstrated that mTOR inhibition reverses HCM in NSML mice. We report for the first time on the effects of treatment with a rapamycin analog in an infant with LS and a malignant form of HCM. In the boy, progressive HCM was diagnosed during the first week of life and diagnosis of NSML was established at age 20 weeks by showing a heterozygous Q510E mutation in the PTPN11 gene. Immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 20 publications
3
51
0
Order By: Relevance
“…Similarly, NSML mouse models that present with HCM have been reported to respond to inhibition of the mTOR pathway using rapamycin (25). Clinical studies also have reported that treatment with a rapamycin analog in a NSML patient improved cardiomyopathy and decreased brain natriuretic peptide levels in serum (26). Whereas treating the cardiac defects for NS or NSML might require distinct therapeutic regimens, our data suggest that in conditions in which either NS-or NSML-related cardiac dysfunction is suspected, a single therapeutic such as dasatinib might provide a novel strategy to improve cardiac functionality.…”
Section: E846kmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, NSML mouse models that present with HCM have been reported to respond to inhibition of the mTOR pathway using rapamycin (25). Clinical studies also have reported that treatment with a rapamycin analog in a NSML patient improved cardiomyopathy and decreased brain natriuretic peptide levels in serum (26). Whereas treating the cardiac defects for NS or NSML might require distinct therapeutic regimens, our data suggest that in conditions in which either NS-or NSML-related cardiac dysfunction is suspected, a single therapeutic such as dasatinib might provide a novel strategy to improve cardiac functionality.…”
Section: E846kmentioning
confidence: 96%
“…Given the clinical importance there has been significant interest in developing pharmacological treatments for cardiomyopathies in NS and NSML (24). It has been shown that inhibitors of the Akt/mTOR pathway can ameliorate HCM in the NSML model (25,26), whereas, genetic interference with, or pharmacologic inhibition of, MEK/ERK in a NS mouse model suppresses the development of CHD (27)(28)(29)(30). Uncovering targets and subsequently viable pharmacological therapies that encompass the overlapping clinical spectra between NS and NSML should fulfill a significant unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…44 Recently, the first trial of a mTOR inhibitor was reported in an infant with NSML and rapidly progressive HCM with a goal of halting progression of hypertrophy and outflow tract obstruction until the time of transplant. 45 An understanding of the genetic basis of HF in this case led to trial of a pathway specific inhibitor for treatment.…”
Section: Overlapping Causesmentioning
confidence: 97%
“…An inhibitor of mammalian target of rapamycin has been shown to reverse heart defects in both a mouse model of 74 and in an individual with NSML. 75 Histone demethylase inhibitors that might not be directly associated with the RAS/ERK pathway have also been shown to ameliorate the phenotype of a mouse model of CFC syndrome. 73 Further studies will explore the pathogenetic mechanisms behind and therapeutic approaches for RASopathies.…”
Section: Rasa1mentioning
confidence: 98%